Photosynthetic parameters and stomatal conductance in attached and detached balsam fir foliage. Issue 4 (5th August 2021) - Akalusi, Matthew E.; Meng, Fan‐Rui; P.‐A. Bourque, Charles
Abstract: Leaf level gas‐exchange measurements can be made on detached foliage to address the challenge of access to the crown of tall trees. However, detachment may impact leaf gas exchange. This necessitates the study of gas‐exchange characteristics of foliage on detached branches to assess the feasibility of using detached branches for gas‐exchange analysis. We compared photosynthetic parameters and stomatal conductance in foliage of attached and detached branches of balsam fir [ Abies balsamea (L.) Mill.] during the growing season. Data were analyzed using a linear mixed‐effect model, with fixed and random effects (branch status and measurement month, and tree number, respectively). Branch detachment had no significant effects on: (i) photosynthesis at the current ambient CO2 concentration (400 µmol mol −1, A 400 ); (ii) maximum rates of Ribulose‐1, 5‐bisphosphate (RuBP) carboxylation ( V cmax ) and regeneration ( J max ); (iii) the ratio of J max to V cmax (i.e., J max : V cmax ), and (iv) stomatal conductance ( g s ) during the study period ( p = 0.120–0.335). There was a strong seasonal effect on all gas‐exchange variables ( p ≤ 0.001–0.015). Gas‐exchange measurements made on detached foliage during the warm summer months should be performed with care. Reliable gas‐exchange measurements can be obtained using balsam fir foliage on detached branches 50–80 cm in length, in cooler growing‐season months, up to 30 min after detachment.